Structural behaviour of post-earthquake steel plate shear wall repaired by non-welded oblique stiffeners. (May 2022) - Yu, Jinguang; He, Lewei; Li, Bo; Li, Lei; Tian, Limin; Men, Jinjie
Abstract: A two-stage experimental study was conducted to investigate the structural behaviour of two single-span two-storey steel plate shear wall (SPSW) specimens repaired by non-welded oblique stiffeners. In stage Ⅰ, both SPSW specimens were subjected to a quasi-static load to simulate the damage under an earthquake attack. Afterwards, the infill panels in one SPSW specimen were repaired and stiffened by non-welded oblique stiffeners (i.e., specimen OR-SPSW). The damaged SPSW specimens with or without repair were subjected to cyclic load to evaluate the effectiveness of the repair method in stage II. The seismic performance of two SPSW specimens was compared in terms of initial stiffness, bearing capacity, energy dissipation capacity and out-of-plane deformation of infill panels. Test results indicate that the residual out-of-plane deformations of infill panels were effectively restrained after the installation of oblique channel steel. The bearing capacity of specimen OR-SPSW was 11.06% higher than that without repair. In addition, the finite element analysis was performed to further investigate the seismic performance of the SPSW structures repaired by various types of stiffeners, including oblique multi ribs, orthogonal and oblique channel steel. The simulation results indicate that using the three types of stiffeners is able to restore the seismic behaviour of SPSW structures, while using the oblique multi-rib stiffeners is the most effective method in restraining the out-of-plane deformation of infill panels and increasing the bearing capacity. However, the orthogonal channel steel stiffener can contribute to little enhancement of the structural bearing capacity. Besides, the bearing capacity of the SPSW structure repaired by the oblique multi-rib stiffeners was 14.29% higher than that with the oblique channel steel stiffeners.